An investigation of sqrt 2 conjecture inspired drag induced vertical axis wind turbine blade - Ashwindran Naidu, Sanderasagran (2023)
Governments and research agencies are providing support and resources to facilitate the growth of renewable energy sector (RES). Today wind turbines (WT) are the prominent form of renewable energy for direct energy harvesting. It is found that traditional Savonius wind turbine (SWT) requires design modification or integration supportive design feature in order to improve the drag attributes and power output performance. Generally conventional WTs are design to operate at high wind speed ranging from 10-15 m/s. This constrains the WT to harvest adequate power at low wind speed condition. Research shows that, design configuration adjustment and optimization has improved the efficiency in Cp. Hence, in this study drag driven WT configuration namely SWT is adapted for the construction of proposed design. The research process flow is segregated into four phases specifying the strategies utilized to carry out the investigation namely bio-hybridization, experimental fluid dynamics, computational fluid dynamics and optimization. The selected bio-elements are reconfigured and altered to fit the design problem and criteria of WT. Since the study involves analyzing and recognizing complex morphologies of bio-elements, computational based framework is utilized for the geometry extraction process namely OpenCV. The proposed drag induced wind turbine (DIWT) is a result of hybridization of two bio-elements namely nautilus spiral configured shell and barnacle marine organism. The aim of primary stage of the design process is to construct the mainframe of the WT blade shape which is extracted from a non-aerodynamic element which is Nautilus shell. The initial design is modelled with barnacles and blade morphology inspired by mathematical conjecture but without endplates. The proposed conjecture and ratio provide an alternative approach in calculating the parametric values of a geometry with regards to √2. It appears that irrational number √2 is fundamental in the creation of circle and spiral. In addition, multiple combinations of blade curvatures is also possible to be constructed with the newly found conjecture, ratio and method. Meanwhile, relative to experimental fluid dynamics procedure the rotational properties of the rotor is investigated using a digital torquemeter coordinated by Arduino. The credibility of the fabricated torquemeter is investigated by comparing the generated moment magnitude with computational numerical model which is executed in CFD. The percentage of error between computational and instrumentational torque is 15.6 %. As for CFD framework for this research, the initially proposed design is comprehensively investigated based on computational numerical model analysis conducted in Ansys CFX. Preliminary investigation indicated that the performance of the initial design is affected by the absence of endplate. The barnacle geometry and its configuration introduce early turbulence and consequently reduces the pressure drag. The reconfiguration of the design is based on the proposed optimization process. The basis of the optimization technique is the Gf which governs the drag attributes of a body relative to flow. If the researcher would like to further investigate reconfigure the existing morphology, it is required to determine the body geometric factor in order to preliminary determine the drag condition. Since Gf < 1 (negative volume) and Gf > 1 (positive volume) minimizes the drag attributes if the orientation of the body is perpendicular the flow. It is found that the implementation of the barnacle geometry aligned perpendicular to flow effectively reduces the pressure attributes. Hence, the technique inspired for the removal of the barnacle geometry. It is found that the blockage corrected peak Cp value of the reconfigured turbine is 0.201 which is 15.4 % of deviation from the uncorrected CFD result. Hence the new corrected data of Cp is utilized to compare with available literature to measure the performance of the proposed design. It can be concluded that the optimized design improved the quality of Cp by 19.2 % in comparison to conventional SWT at λ = 0.67. Meanwhile the author also presented a novel design with shaft and adjoin blade. It is found that the optimized design outperformed both the models by 15.51 % and 6.34 % respectively. Hence, it is evident that blade morphology modification via the proposed conjecture with the presence of endplate improves the performance of the rotor in terms of rotational characteristics and power output.